Ethnobotanical study of traditional medicinal plants used to treat human ailments in West Shewa community, Oromia, Ethiopia - Beressa, Tamirat Bekele; Gadisa, Diriba Alemayehu; Mammo, Siraj; Umeta, Gurmu Tesfaye; Meskele, Lemma Bose; Gudeta, Biruk Mosisa; Taye, Getu Melesie (Frontiers in Pharmacology, 2024)
Plants have formed the basis of traditional medicine (TM) systems, which have been used for thousands of years. According to reports, one-quarter of the commonly used medicines contain compounds isolated from plants. This study aims to identify and document the plants for ethno-pharmacological use by the indigenous communities of West Shoa Zone, Oromia region, Ethiopia. The cross-sectional study was conducted from November 2020 to November 2021 in West Shewa Zone, Oromia Region, Ethiopia. The ethnobotanical data was collected from Ejere District, Ada Berga District, Dandi District, Ambo District, Ambo Town, Toke Kutaye District, and Bako Tibe District. A descriptive statistical method (percentage and/or frequency) was employed to summarize ethnobotanical data. Moreover, the informant consensus factor was computed. Microsoft Excel spreadsheet software (Microsoft Corporation, 2016) and SPSS (version 25) were used to organize and analyze the data. In the study area, a total of 51 families of medicinal plants with 113 genera were identified.Fabaceae (10 species), Asteraceae (7 species), Cucurubitacieae (7 species), Solanaceae (7 species), and Lamiaceae (7 species) were the frequently reported medicinal plants. The leaf (57.2%) was the most widely used medicinal plant parts, and oral administration (56.5%) was the most cited route of administration. In the present study, most of the medicinal plants were used fresh, which was (75%) and the most common disease the healers treated was gastrointestinal disease, followed by skin disease and febrile illness. The major threat to medicinal plants in the study area was agricultural expansion, which was reported by 30.6% of the respondents. The study area was rich in medicinal plants, Fabaceae which commonly used family. Most of the medication prepared by the traditional healers was taken orally and derived from the leaf part of the medicinal plant. Since this research is a preliminary study -3 -| P a g e which will be used as a base for further study. The efficacy and safety of the medicinal plant claim should be studied in the future.